The Research of the Functional Positioning of Vocational Education of Undergraduate Level - Zhao, Jing (Journal of Theory and Practice of Contemporary Education, 2024)
Vocational education of undergraduate level is an important measure to adapt to economic and social transformation and upgrading, and a key link to break through the "ceiling" of vocational education. Vocational education of undergraduate level is a new member of diversified higher education system and an important turning point in the construction of modern vocational education system. For vocational colleges and universities, it is very important to clarify and fulfill the function of vocational education at undergraduate level and cultivate high-quality technical talents in line with social needs. Many designs are only satisfying some transient desires, while people's real needs, long-term needs are often neglected. According to Maslow's needs principle, the need for life safety is the most important human need. Human security needs include a sense of certainty, a sense of security and a sense of control, which refer to a person's awareness, understanding and categorization of the objective properties of things themselves or the objective laws of things that are about to happen, respectively. The three together constitute the hierarchy of human security needs. Internet platforms have harvested a lot of capital and dividends while gaining a lot of traffic and attention. The platform should also face up to the problems that exist now and do their best to take up the responsibility that the platform should have. Only under the premise of ensuring the most basic safety and security of users can we really reap the long- term high-quality development.